PERAN GURU AKIDAH AKHLAK DALAM MENGATASI MASALAH KENAKALAN SISWA (STUDI KASUS) DI KELAS VII MADRASAH TSANAWIYAH (MTS) NURUL IKHSAN YAFADLILLAH SULURSARI KECAMATAN GABUS KABUPATEN GROBOGAN TAHUN PELAJARAN 2021/2022 - Meita Setiyaningsih; Moh Nurdhuka (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2020)
The role of the school is very important in shaping the behavior of its students. The school functions as a facilitator who will lead students so that they can excel with faith, knowledge and charity. In schools, the role of teachers of moral aqidah is needed in guiding and directing their students, especially regarding morals. Adolescence is an act or crime or violation committed by a teenager against legal norms, social norms, group norms. The delinquency that occurred at MTs Nurul Ikhsan Yafadlillah took various forms. So it is necessary to hold countermeasures so that they do not become negative attitudes and actions. This study aims to (I) to find out the factors that cause delinquency in class VII students at Madrasah Tsanawiyah (MTs) Nurul Ikhsan Yafadlillah Sulursari, Gabus District, Grobogan Regency for the 2021/2022 Academic Year. (II) To find out the role of moral aqidah teachers in overcoming the problem of delinquency in Class VII students at Madrasah Tsanawiyah (MTs) Nurul Ikhsan Yafadlillah Sulursari, Gabus District, Grobogan Regency for the 2021/2022 Academic Year. This research is a qualitative descriptive research with the type of case study research. The data obtained from this study include: To find out the factors that cause delinquency in grade VII students at Madrasah Tsanawiyah (MTs), and the role of the teacher of moral aqidah in overcoming the problem of delinquency in Grade VII students at Madrasah Tsanawiyah (MTs). The data collection method used by the author is Observation, Interview, and Documentation. After analyzing the data, the following conclusions were obtained: First, the role of the moral aqidah teacher is effective in participating and being active in overcoming student delinquency. Second, the factors that cause and inhibit the occurrence of student delinquency are family factors, school factors, and community factors.